Perspectives on Landscape Approaches in Indonesian Policies - Maryani, R.; Djaenudin, D.; Lugina, M.; Indartik; Moeliono, M.; Yuliani, E.L. (P3SEKPI, 2021)
Indonesian national development planning is laid out in five-year planning documents. These documents form the points of reference for implementation. The current plan (2020 – 2024) stipulates environmentally friendly economic development with the intention of integrating conservation and economic development; two aims frequently deemed contradictory (O’Connor et al. 2020). Sustainable development aims to ensure synergy and optimize the achievement of often conflicting economic, social, and environmental objectives. The landscape approach focuses on means and processes for managing the complexities and dynamics of related biophysical, social and policy elements in overcoming trade-offs in the utilization of natural resources and achieving environmentally friendly development. Its overall aim is sustainable landscape management.